Звіт про діяльність Національної академії наук України у 2015–2019 роках - Патон, Б.Є. (Вісник НАН України, 2020)
Відповідно до Статуту Національної академії наук України, 13–17 квітня 2020 р. мала відбутися сесія Загальних зборів НАН України та загальних зборів відділень НАН України. Однак у зв'язку з тимчасовою забороною проведення масових зібрань, зумовленою запобіганням поширенню коронавірусної інфекції, постановою Президії НАН України чергову сесію Загальних зборів НАН України та загальних зборів відділень НАН України відтерміновано до поліпшення епідемічної ситуації в країні та закінчення дії обмежувальних заходів. Журнал «Вісник НАН України» публікує підготовлені до сесії Загальних зборів НАН України матеріали, в яких висвітлено основні підсумки діяльності у 2015–2019 рр. Академії загалом та результати діяльності секцій, відділень наук, регіональних наукових центрів зокрема. According to the Statute of the National Academy of Sciences of Ukraine, a session of the General Meeting of the National Academy of Sciences of Ukraine and the General Meeting of Departments of the National Academy of Sciences of Ukraine was to take place on April 13–17, 2020. However, due to the temporary ban on holding mass gatherings to prevent the spread of the coronavirus infection, the resolution of the Presidium of the NAS of Ukraine postponed the regular session of the General Meeting of the NAS of Ukraine and the General Meeting of the Departments of NAS of Ukraine until an improvement in the epidemic situation in the country and expiration of restrictive measures. The journal “Bulletin of the NAS of Ukraine” is publishing materials prepared for the session of the General Meeting of the NAS of Ukraine, which highlights the main results of the Academy in 2015–2019 and the results of sections, science departments, regional research centers in particular.